Developing and validating halal service quality instrument for Malaysian food service establishments: a conceptual paper - Ibrahim, Shahariah; Othman, Mohhidin (Elsevier, 2014)
Thus far no effort has been undertaken to facilitate foodservice operators to measure their performance, identify and deploy appropriate measures to improve the requirements and expectations of a Halalan Toyyiban Foodservice modus operandi. This paper looks into developing the tools to measure the Halal Foodservice Service Quality based on previous literature and in-depth interviews to be conducted among selected Muslim Clergies and the general public followed by validation process using statistical analysis. This tool could be used to minimize the occurrence of halal service failures, improve recovery efforts, increase customer satisfaction, and generate positive re-patronage behaviour at food service establishments.